Physical education and language development - Becker, Werner; Sahr, Romain (Pedagogika, 2014)
Based on the hypothesis that in addition to increasing physical competence, intensified sports activity also promotes the development of general cognitive ability, the project’s primary goal was to determine the current physical and language learning levels of the participating students and focus on their potential and on their acquisition of competences in the development of language skills accompanied by regular participation in sports activities. Due to the extraordinary interdependencies between physical education and language learning, focus on the mediation of key qualification, particularly in the social environment where the study took place, should be intensified.